2017
DOI: 10.1128/jvi.00062-17
|View full text |Cite
|
Sign up to set email alerts
|

A Temperature-Sensitive Lesion in the N-Terminal Domain of the Rotavirus Polymerase Affects Its Intracellular Localization and Enzymatic Activity

Abstract: Temperature-sensitive (ts) mutants of simian rotavirus (RV) strain SA11 have been previously created to investigate the functions of viral proteins during replication. One mutant, SA11-tsC, has a mutation that maps to the gene encoding the VP1 polymerase and shows diminished growth and RNA synthesis at 39°C compared to that at 31°C. In the present study, we sequenced all 11 genes of SA11-tsC, confirming the presence of an L138P mutation in the VP1 N-terminal domain and identifying 52 additional mutations in fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…A priming loop (residues 557-567), also known as a ''primer grip," situated at the joining site of thumb and palm subdomains, has a flexible structure that interacts with triphosphates during initiation. The catalytic activity of VP1 is enhanced by the interaction between the residue Leu138 of NSP1 protein with NSP2/NSP5 nonstructural proteins under physiological condition [60]. Our analysis revealed that the mean PPID of the RdRp protein is rather low (3.1%) {Table 1}, this protein is having compact globular structure with few predicted MoRFs in its polymerase domain (residues 393-407 and 463-471) that may be responsible for the polymerase activity {Fig.…”
Section: Examination Of Intrinsic Disorder In Rotavirus Structural Prmentioning
confidence: 89%
“…A priming loop (residues 557-567), also known as a ''primer grip," situated at the joining site of thumb and palm subdomains, has a flexible structure that interacts with triphosphates during initiation. The catalytic activity of VP1 is enhanced by the interaction between the residue Leu138 of NSP1 protein with NSP2/NSP5 nonstructural proteins under physiological condition [60]. Our analysis revealed that the mean PPID of the RdRp protein is rather low (3.1%) {Table 1}, this protein is having compact globular structure with few predicted MoRFs in its polymerase domain (residues 393-407 and 463-471) that may be responsible for the polymerase activity {Fig.…”
Section: Examination Of Intrinsic Disorder In Rotavirus Structural Prmentioning
confidence: 89%
“…9B and C). The most extreme differences were detected in a modeled flexible surface-exposed loop (strain SA11 aa 346 to 358) of the PD (31). Specifically, residues 347, 349, and 352 were predicted to have reduced dynamical movement for all of the alanine mutants compared to WT VP1.…”
Section: Figmentioning
confidence: 99%
“…Molecular dynamics simulations were performed using the program GROMACS 2018 on a modified atomic model of VP1 (PDB accession no. 2R7Q), described by McKell et al (22,31). The UCSF Chimera software program was used for all visualizations and to generate mutants with Chimera's Rotamers tool, as previously described (32).…”
Section: Generation Of Rvp1-and Rvp2-expressing Baculovirusesmentioning
confidence: 99%
“…The importance of amino acid residues that affect the activity of VP1 protein has been demonstrated [7,[10][11][12] and mutant VP1 proteins in specific positions were engineered in order to assess their capacity to synthesize dsRNA in vitro [10,11]. Authors reported that, based on their effect on the replication level, the induced mutations can be classified into three groups: (i) mutations with no significant effect on replication level; (ii) mutations significantly lower levels of dsRNA product; and (iii) mutation that enhanced the initiation capacity and product elongation rate of VP1 protein.…”
Section: Introductionmentioning
confidence: 99%